Archivos, derechos humanos y memoria : una revisión de la literatura académica internacional (2017)
ABSTARCT: This article features a summary of studies produced over the last two decades that research the relationships between archives, human rights and collective memory. The analysis of the numerous works that address these three categories was classified into four approaches: 1) the concept of archives as evidence of human rights violations; 2) a critical evaluation of the role of documents, archives and archivists in building collective memory; 3) social justice as a guide of archival praxis; and 4) archives as places of memory and territories of dispute related to different senses of the past.